Two-year experience in laparoscopic colorectal surgery in a healthcare service in Salvador: a critical analysis - Mendes,Carlos Ramon Silveira (2013)
INTRODUCTION: laparoscopic colorectal surgery has become a viable access route since the beginning of 1990, using Jacobs' technique. Its outcomes are decrease in hospitalization length, early return to routine activities, better esthetic results and less postoperative pain. OBJECTIVE: to report a series of patients treated by a team using videolaparoscopic access route in colorectal surgery. MATERIAL AND METHODS: retrospective, descriptive study carried out in Salvador, state of Bahia, Brazil, from April of 2010 to May 2012. RESULTS: a total of 81 procedures were analyzed; 59.3% of cases were females, mean age was 58.3 years. Benign illness was treated in 48.1% to the patients. Rectosigmoidectomy was carried out in 41.5% and right colectomy in 21%. Intraoperative complications were observed in 3.7% and postoperative in 21% of cases, with a conversion rate of 6.2%. CONCLUSION: the laparoscopic procedure showed to be safe and the surgeon's training results in better outcomes in this series.